Aux marches du théâtre : affiches sensationnelles et posters énigmatiques dans Aurora Floyd de M. E. Braddon - Laurence Talairach (Cahiers Victoriens et Edouardiens)
Throughout the 1860s, Victorian England strove to foreground the image of its society as some kind of Crystal Palace where transparency and truth prevailed. With fast-growing industrialisation and massive urbanization, it was indeed harder and harder to read through class codes, and external appearances less and less matched reality. The figure of the actress is thus a significant example crystallizing nineteenth-century anxieties : gliding from role to role and playing on subversive shifts of identity, she seems to haunt the Victorian literary stage, proposing a threatening version of womanhood. Naturally enough, she is a recurrent character in sensation fiction — a popular genre which precisely exposed the gap between appearances and reality, anchoring secrecy at the very core of the middle classes.